Meningkatkan Hasil Belajar Matematika tentang Konsep Pecahan melalui Media Kartu di Sekolah Dasar - Caswita Caswita; N. Oon; Husni Mubarok; Dodo Murtado; Yanto Maulana Restu (Simpati, 2026)
This study was conducted at SD Negeri Gunungkoneng, Cihideung District, Tasikmalaya City, in mathematics learning on the topic of fractions using card media. The research subjects were 53 fourth-grade students. The study was motivated by the low learning outcomes of students in the topic of fractions, particularly in the indicator of adding fractions with the same denominator, which achieved an average score of only 52.1. The study aimed to examine the planning, implementation, and improvement of students' learning outcomes through the use of card media in teaching fraction concepts. Data were collected through a pre-test to measure students' initial abilities, observation sheets to assess lesson planning, teacher performance, and student activities during the learning process, and a post-test to measure improvements in learning outcomes. The results showed a significant improvement in students' average scores, increasing from 53.02 before the intervention to 65.09 after the first cycle and 79.06 after the second cycle. In addition to improving learning outcomes, the use of card media also enhanced students' attitudes and behavior during the learning process. The findings suggest that card media can serve as an alternative instructional model that may be further developed for other learning materials and contribute to improving the quality of instruction as well as the professionalism of elementary school teachers.